A flickering cutaneous lesion occurring after an insect bite - Tymen Hodde (Wiley, 2021)
Abstract Many exaggerated skin reactions after insect bites have been described and due to global warming the incidence of these cases will increase. This clinical video promotes its recognition by showing an unusual cutaneous phenomenon after an insect bite.